A CASE REPORT: THE STAGED RETRO AURICULAR FLAPS FOR AURICLE RECONSTRUCTION AFTER TRAUMATIC AMPUTATIONS - Alexandria Stephanie Suparman; Doni Setiawan; Yugos Juli Fitra (Jurnal Rekonstruksi dan Estetik)
Highlights: